Painting of the famous Chintamani Temple of Bikaner - Temples of India Project Team (Jio Institute, 2024)
The horizontal lowest band, of the ceiling of the mandapa (pillared hall) of Bhandasar Temple, is a painting of the famous Chintamani Temple of Bikaner. Drawn as a two-dimensional object, the painting portrays the temple structure as two 2D. The face of the pillar capital in the image has a Shrivatsa symbol, one of the eight auspicious Jain symbols.